الاجتهاد القضائي الجزائري في احكام الالتزام - - السعدي سعودي (جامعة المسيلة, 2022)
نص قانون الأسرة الجزائري على التنزيل الذي يعني إعطاء الأحفاد نصيبا من تركة جدهم أو جدتهم تعويضا لهم عمّا فاتهم من ميراث والدهم أو والدتهم الذين توفيا في حياة هذا الجد أو الجدة وحجبوا بأعمامهم أو عمّاتهم بقوا في فقر وحاجة، وهذا الاستحقاق يكون بشروط محددّة، وبمقدار معيّن يساوي في الأصل نصيب مورثهم لو بقي حيا على أن لا يتجاوز هذا النصيب في أقصى حالاته ثلث التركة، لكن النصوص القانونية ليست كافية وفيها عجز تشريعي أثار الكثير من المشاكل في تطبيق أحكام التنزيل عمليا ممّا استدعى تدخل القضاء لفض هذه النزاعات من خلال اجتهاداته في تفسير هذه المواد وحتى من خارجها من أجل إحقاق الحق وتحقيق العدالة المنشودة وحماية المراكز القانونية لكل إنسان، استنادا لمصادر الاجتهاد الرسمية، وبيان دور مؤسسة والقضاء ممثلة في شخص القاضي في حل النزاعات المتعلقة بالتنزيل وحسم الكثير منها حسما نهائيا. الكلمات المفتاحية: الاجتهاد القضائي ـ التنزيل ـ الميراث ـ الأحفاد ـ الوصية. summary The Algerian family law stated the “Tenzil“(mixture between the commandment and the legacy) which means giving the grandchildren a share of their grandfather’s or grandmother’s inheritance in compensation for what they missed from the inheritance of their father or mother who died in the life of this grandfather or grandmother and were withheld by their uncles or aunts who remained in poverty and need.This entitlement depends to specific conditions and it is defined to certain amount that originally equal to what they bequeathed if their parents were still alive provided that this amount, in its most extreme case, does not exceed a third of the estate. But the legal texts are not enough and there is a legislative deficit that raised many problems in practical applying of the Tenzil provisions. This obstacle necessitated the intervention of the judiciary to resolve these disputes through its jurisprudence in the interpretation of these articles, even from other sides, in order to implement the right, to achieve the desired justice, and to protect every human being legally. The official sources of jurisprudence work side by side of the legislative institution represented by the judge in order to resolve disputes related to the Tenzil and put an end to them as well. Keywords: Judicial Jurisprudence - Tenzil - Inheritance - Grandchildren - commandment.
Keywords: ـ التنزيل ـ الميراث ـ الأحفاد ـ الوصية.